Contemporary Issues in Linguistics: A Systematic Literature Review on Emoji and Emoticon: - Setyawan, Harits; Musthafa, Bachrudin (Universitas Lancang Kuning, 2024)
This research aims at reviewing the previous studies on emojis and emoticons in computer-mediated communication to provide information the extent to which they have been studied, as well as proposing a new concept for investigation and how it is implemented in research. To answer the research objectives, the author reviewed articles about emojis and emoticons published from 2012-2021. The data are collected by using an application called Publish and Perish, as well as free social networking sites ResearchGate and Academia. The findings of the previous research are then synthesized. The research results show that the differences and similarities of emojis and emoticons, as well as which of them is used more often and why one of them is preferred have been investigated. Both emojis and emoticons are used to express emotion, clarify meaning, substitute texts and punctuations. Then, the use of emojis and emoticons is influenced by social relationships, level of formality and gender, emotional relationships, social media platforms, and linguistic patterns. Despite that, emojis and emoticons are not used correctly in terms of the meaning contained in them and have not been much studied by using linguistic theories. It implies that more research on emojis and emoticons which is paired with linguistic theories is needed. For that reasons we propose that the myth which emerges as the folded hand emoji is used and why the myth emerges are studied in the future research.